Compensation to Fulfill Voltage Drop Security in Medium Voltage Feeders - Hermagsantos Zein; Sri Utami; Siti Saodah; Conny Kurniawan Wachjoe (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2022)
Increasing the load or expanding the feeder can increase the voltage drop. In addition, the greater the flow of reactive power on the line, the worse the voltage drop. On the other hand, the voltage must meet certain safety limits, and one way to correct the voltage drop is to apply for compensation. However, calculating the voltage drop through the power flow and the measurement methods is difficult to apply because it is necessary to determine the value of the amount of load on each node. This paper will propose a simple method that is convenient to apply to determine the compensation needed to maintain voltage quality in medium voltage feeders. The methodology used is a current source approach that functions as a variable. Then the current flow along the channel is assumed as a linear function so that the load center point is obtained according to the feeder configuration and load capacity. The simulation results on the 21-node feeder assuming a power factor of 0.8, show that the voltage drop improvement is quite effective with compensation. For example, at a 150 A current source, with 30 A compensation, the voltage drop can be increased from 4.45% to 3.98%. Furthermore, by applying for compensation, it is possible to expand the load to a source current of 165 A with a compensating current of 80 A.